A review of Amblypalpus and Priscapalpus (Acari: Trombidiformes: Tenuipalpidae), including two new species of Amblypalpus from Iran - Farzan, Sadegh; Asadi, Mahdieh; Ueckermann, Edward A.; Seeman, Owen D.; Beard, Jennifer J. (Zootaxa, 2013)
Two new species of Amblypalpus (Acari: Trombidiformes: Tenuipalpidae) are described from Iran: Amblypalpus iraniensis sp. nov., from Wild Almond, Amygdalus scoparia (Rosaceae), and Amblypalpus thymus sp. nov., from Common Thyme, Thymus vulgaris (Lamiaceae). The new species are classified tentatively in Amblypalpus. The species Priscapalpus thomissus Meyer, 1979 is transferred to Amblypalpus and the genus concept of Priscapalpus is narrowed and therefore redefined. Similarly, we present an expanded concept of Amblypalpus. A key to brevipalpine genera and Amblypalpus species is provided.